Mind your app: Could plant ID applications lead to an increase in extinction risk? - Berjano, Regina; López-Tirado, Javier; Martín-Escobar, Irene; Martínez-Sagarra, Gloria; Nieto-Lugilde, Diego; Sánchez-Romero, Jimena; Estrella, Manuel De La (Phytotaxa, 2023)
N/A